Expression of Lanosterol 14-Demethylase (ERG11) Gene of Three-Drug Combinations in Candida albicans: Three-Drug Combinations in Candida albicans - Alizadeh, Fahimeh; Khodavandi, Alireza; Ahmadsomali, Sahar (Iranian Journal of Pharmaceutical Sciences, 2019)
Patients with impaired immunity are at particular risk of infections with Candida albicans. Antifungal drugs such as azoles commonly used for candidiasis treatment, but drug resistance is one of the most common problems for public health. The aim of this study was to evaluate the expression of lanosterol 14-demethylase (ERG11) gene for three-drug combinations in C. albicans. Disk diffusion and broth microdilution susceptibility tests were employed to evaluate the synergic effects of amphotericin B, fluconazole, voriconazole, ketoconazole and itraconazole. Quantification of ERG11 gene expression was carried out in C. albicans treated with threedrug combinations of fluconazole/ ketoconazole/ voriconazole and fluconazole/ ketoconazole/ itraconazole.Three-drug combinations revealed synergistic and partial synergistic effect for all tested isolates (FIC index range of 0.27-0.77). The expression levels of ERG11 were down-regulated by three-drug combination of fluconazole/ ketoconazole/ voriconazole treatment. Fluconazole synergizes with ketoconazole and voriconazole in three-drug combination against C. albicans by targeting of the ERG11 gene.